A Normative Analysis of DSN-MUI Fatwa No. 154/DSN-MUI/V/2023 and Its Implications for Sharia ETF Governance in Indonesia - Setiawan bin Lahuri; Alfi Khilmi Khusnia; Yulizar Djamaluddin Sanrego; Khoirul Umam; Muchammad Taufiq Affandi (Al-Muamalat, 2026)
The rapid development of Islamic finance has increased demand for Sharia-compliant investment instruments, including Sharia Exchange-Traded Funds (ETF). In Indonesia, Sharia ETF governance faces regulatory fragmentation and legal uncertainty, particularly concerning the integration of Sharia principles into capital market regulations. Existing studies have predominantly examined performance aspects or formal compliance processes, while the role of fatwas as operational governance instruments remains understudied. This research examines the National Sharia Board-Indonesian Council of Ulama (DSN-MUI) Fatwa No. 154 of 2023 as a Sharia governance instrument. A normative juridical approach is employed to analyze the provisions within the fatwa, Financial Services Authority (OJK) regulations, and operational practices of Sharia ETF on the Indonesia Stock Exchange (IDX). Data analysis was conducted using thematic methods based on the dimensions of Sharia governance, transparency, and law enforcement. The findings indicate that although Fatwa No. 154 provides legal clarity and certainty, the fatwa remains at a normative level and lacks operational standards that can be implemented in disclosure, reporting, and supervision aspects. Consequently, Sharia compliance risks ceasing at a formalistic stage without effective integration with capital market regulations. This research contributes to Islamic financial governance literature by offering a conceptual framework that positions fatwa as a regulatory instrument within Sharia capital market governance. The implications emphasize the need for regulatory strengthening and enhanced inter-institutional coordination to realize more effective Sharia ETF governance.